Effect of backcutting on surface roughness during high speed end milling - Afifah binti Mohd. Ali (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
In industrial machining processes, milling is a fundamental machining operation and end milling is the most common metal removal operation encountered. It is widely used in a variety of manufacturing industries including the aerospace and automotive sectors, where quality is an important factor in the production of slots, pockets, precision molds and dies. The quality of the surface plays a very important role in the performance of milling as a good-quality milled surface significantly improves fatigue strength, corrosion resistance, or creep life. This research concentrated on the issue of surface machined quality and the effort taken to predict surface roughness. The focus will be on the backcutting phenomena that contribute to surface quality. For this analysis purpose, hardened material AISI H13 tool steel with hardness of 48 HRC is chosen for work material. Machining was done at high cutting speed from 150 m/min up to 250 m/min, feed rate 0.05 to 0.15 mm/rev and depth of cut 0.1 to 0.5 mm. The analysis and observation of the backcutting phenomena were done by using optical surface roughness machine and digital camera microscope. To develop the prediction of surface roughness model in high speed end milling machining, Response Surface Methodology (RSM) Model has been used to design the prediction model with parameters generated by using three level full factorials. From the results, the backcutting phenomena has been investigated with significant results with all objectives successfully fulfilled. RSM has been proven to be an efficient method to predict the surface finish during end-milling of H13 tool steel using TiAlN coated carbide tool inserts under dry conditions with the average accuracy of 87.8%.